Imam Abu Hanifah: The Vanguard of Moderation in Islamic Jurisprudence and the Global Dissemination of Moderate Islam - Rizapoor, Habiburrahman; Rahimi, Mohammad Rashid (Fakultas Syariah UINSI Samarinda, 2023)
This article examines the role of Imam Abu Hanifah in the spread of moderate Islam. Through an analytical and descriptive research approach, the study investigates whether Imam Abu Hanifah can be considered one of the prominent scholars of Wasatiah Islam and explores the impact of his views on the dissemination of moderate Islamic teachings worldwide. The article assesses the influence of Imam Abu Hanifah’s teachings on the dissemination of moderate Islam across different regions. Based on the findings, this article concludes that Imam Abu Hanifah can indeed be considered a prominent scholar of moderate Islam. His madhab, rooted in moderation and flexibility, has played a significant role in the spread of moderate Islamic teachings worldwide. Imam Abu Hanifah’s emphasis on contextual understanding and his pragmatic approach to Islamic jurisprudence have resonated with diverse communities and contributed to the acceptance and propagation of moderate Islamic values in different parts of the world. This research contributes to the existing body of knowledge on Islamic scholarship by shedding light on the significant role played by Imam Abu Hanifah in the dissemination of moderate Islam. It underscores the importance of balanced interpretations and contextual understanding in promoting a moderate and inclusive understanding of Islamic teachings. Keywords: Imam Abu Hanifah, Al-Islam Al-Wasatiyyah, Al-Madhhab Al-Hanafi, Al-Islam Al-Mu'tadil